Comparison of Two Techniques in Pediatric Tonsillectomy: Erbe Unipolar Electrocautery and Thermal Welding System - Bahar Dal, Secil; Ekemen, Suheyla; Faruk Unal, Omer; Dal, Teoman (ENT Updates, 2021)
Objective: The aim of our study was to compare the tissue damage in pediatric tonsillectomy operations performed with Erbe unipolar electrocautery (EUE) and the thermal welding system (TWS). Methods: This prospective study included patients who had tonsillectomy for recurrent tonsillitis. In the study, 23 patients had tonsillectomy with EUE and 20 had tonsillectomy with TWS. The Faces Pain Scale (FPS) was used for pain assessment on the 1st, 5th, and 10th days postoperatively. On postoperative 5th and 10th days, the healing process in the operation sites was evaluated according to fibrin coverage of tonsil beds, with the Visual Analog Scale (VAS). The removed tonsil specimens were evaluated by a single blinded pathologist, to determine deepest necrosis depths and thermal effect under a light microscope (Olympus BX41). Results: In the study 23 patients who had tonsillectomy with EUE and 20 patients who had tonsillectomy with TWS were included. There was statistically significant difference in the pain scores between the first and fifth days, and in the morphologic intensity of the thermal effect, in favor of the TWS group (P < .05). The VAS scores of the healing process in the postoperative 5th and 10th days were slightly better in the TWS group, but the difference was not statistically significant (P > .05). Also, there was no statistically significant difference found between the 2 techniques regarding the deepest necrosis depths (P > .05). Conclusions: In our study, tonsillectomy with TWS was found to cause less tissue damage in the surrounding tissue and less pain in the early postoperative period, than EUE.